The spirit of God : the exegesis of 1 and 2 Corinthians in the Pneumatomachian controversy of the fourth century - Haykin, Michael A. G. (Vigiliae Christianae, Supplements, 1994)
The Spirit of God examines the use of 1 and 2 Corinthians by two fourth-century Greek Christian authors, Athanasius and Basil of Caesarea, especially as it relates to the doctrine of the Holy Spirit. The controversy over the nature and status of the Spirit during the latter half of the fourth century is detailed in order to place in context the examination of the way in which the theological concerns of Athanasius and Basil shaped their pneumatological interpretation of the Corinthian correspondence. This examination will be of value to patristic scholars interested in the way that Scripture was employed in the fourth century to hammer out doctrine.